Beyond Social Exchange: Career Adaptability Linking Work Stressors and Counterproductive Work Behavior - Yu, Kun; Liu, Chang; Li, Yuhui (Frontiers in Psychology, 2019)
Drawing upon career construction theory (Savickas, 2002, 2013) and the job demand-control-support model (JDCS; Johnson & Hall, 1988; Van der Doef & Maes, 1999), the present study aims to explore the adaptability resources mechanism of the relationship between work stressors and counterproductive work behavior (CWB). Two-wave data were collected from 305 employees working in the operation department of an e-commerce company. The results showed that career adaptability mediated the relationship between work stressors and CWB against both coworkers (CWB-I) and the organization (CWB-O), going above and beyond the mediation effect of job satisfaction (i.e., an indicator of a social exchange path). Also, the association between career adaptability and CWB-O was stronger among employees who perceived a low (vs. high) level of organizational support. This study sheds light on how work stressors are related to CWBs indirectly through career adaptability. The findings also offer practical advice for organizations to prevent CWBs by developing employees’ adaptability.